Dichotomy and perceptual distortions in absolute pitch ability - Athos, E Alexandra; Levinson, Barbara; Kistler, Amy; Zemansky, Jason; Bostrom, Alan; Freimer, Nelson; Gitschier, Jane (Proceedings of the National Academy of Sciences - PNAS, 2007)
Absolute pitch (AP) is the rare ability to identify the pitch of a tone without the aid of a reference tone. Understanding both the nature and genesis of AP can provide insights into neuroplasticity in the auditory system. We explored factors that may influence the accuracy of pitch perception in AP subjects both during the development of the trait and in later age. We used a Web-based survey and a pitch-labeling test to collect perceptual data from 2,213 individuals, 981 (44%) of whom proved to have extraordinary pitch-naming ability. The bimodal distribution in pitch-naming ability signifies AP as a distinct perceptual trait, with possible implications for its genetic basis. The wealth of these data has allowed us to uncover unsuspected note-naming irregularities suggestive of a "perceptual magnet" centered at the note "A." In addition, we document a gradual decline in pitch-naming accuracy with age, characterized by a perceptual shift in the "sharp" direction. These findings speak both to the process of acquisition of AP and to its stability.